The Influence of A. W. Phillips on Econometrics. - Hendry, D; Mizon, G (Cambridge University Press, 2000)
We commence our section with some personal recollections of our first acquaintanceships [with A. W. Phillips]. Then we turn to a consideration of the many ways in which Phillips influenced econometrics, focusing on three main aspects (control theory, moving-average errors in dynamic models, and exogeneity). For a recent brief history of the development of dynamic modelling at LSE, including Phillips’s role in this, see Mizon (1995); also, Rex Bergstrom relates his work to that of Bill Phillips and notes the stimulus he received in Phillips (1993).